Optimization of ship traffic at berthing areas of maritime container terminals via simulation experiment - Ataollah Shahpanah; Seyed Mojib Zahraee; Nirajan Shiwakoti (Logistics Research, 2019)
Maritime transportation plays a leading role in the movement and minimization of transportation costs of goods between regions. One of the major challenges faced by port managers/operators is the growing number of containers or ship traffic which can affect the port container terminal productivity. Mathematical and simulation based models for berth assignments can help to solve such logistic problems in container terminals. However, existing simulation approaches are computationally intensive for optimizing the relevant factors that may affect the berth operation or port productivity. In this study, we proposed a computationally efficient approach of combining simulation with Design of Experiments (DOE) to optimize the container port productivity. Further, based on a case study of container port terminal in Malaysia, we systematically examined the effect of tug pilots, berths numbers, cranes numbers and type of queue on port container terminal productivity. We found that only berth numbers, crane numbers and type of queue had significant effect on port productivity. It is recommended to adopt low container value, first serve queuing approach for serving the ships. We could achieve a maximum productivity of around 86% through our optimization model. Further, an in crease of about 22% in port productivity as compared to the existing port productivity of the terminal was observed through our method.
Keywords: 650; Maritime Transportation; Container port Terminal; Productivity; Computer simulation; Design of experiments (DOE)